Hubungan Job Performance dan Prestasi Akademik Ketua Himpunan Mahasiswa Jurusan UIN Antasari Banjarmasin - Yanti, Sri Norma (UIN Sultan Aji Muhammad Idris Samarinda, 2022)
An organization is a group of places where individuals have goals and want to achieve the same goals. In the internal organization of the campus is a means of personal development of students in order to broaden horizons and improve intellectual integrity and personality to achieve educational goals The purpose of this study was to determine whether there is a relationship between job performance and academic achievement at the head of the student association majoring in the State Islamic University of Antasari Banjarmasin. The research method used in this research is quantitative with correlational method. The results of the correlation test obtained a significance value of 0.001 < 0.05 so that the proposed hypothesis was accepted. The results of the hypothesis test showed a calculated r value of 0.161, which means that the relationship between variables has a strong level of relationship.